2021
DOI: 10.1002/ange.202014027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Templates on the Selective Formation of Zeolite Oligomers

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The calculation finely reproduced previous results on thermostability of PAs. Consistent with recent investigations, Δ G f of t2 is slightly positive and nearly thermal neutral, suggesting that t2 would be slightly less plausible with respect to OA (Figure ) and its concentration would be lower than OA at steady state. , However, the energy barriers for t2 formation and hydrolysis into t1­(OA) are similar and higher than ∼60 kJ/mol, showing that a large portion of t2 may exist for further evolution. The calculated Δ G f of t3 and c3-3-1 are −13.5 and −16.9 kJ/mol, respectively, at 298.15 K (Table ) and are in reasonable agreement with the reported Δ G when the formed H 2 O was treated explicitly. ,, The slight difference can be attributed to the theoretical implementation and computational setups.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The calculation finely reproduced previous results on thermostability of PAs. Consistent with recent investigations, Δ G f of t2 is slightly positive and nearly thermal neutral, suggesting that t2 would be slightly less plausible with respect to OA (Figure ) and its concentration would be lower than OA at steady state. , However, the energy barriers for t2 formation and hydrolysis into t1­(OA) are similar and higher than ∼60 kJ/mol, showing that a large portion of t2 may exist for further evolution. The calculated Δ G f of t3 and c3-3-1 are −13.5 and −16.9 kJ/mol, respectively, at 298.15 K (Table ) and are in reasonable agreement with the reported Δ G when the formed H 2 O was treated explicitly. ,, The slight difference can be attributed to the theoretical implementation and computational setups.…”
Section: Resultssupporting
confidence: 84%
“…With the promotion of amines, the reaction switches to a two-step S N 2-like mechanism with five-coordinated Si species stabilized as intermediates and the barriers also change to ∼60 kJ/mol . Similar barriers were also reported by Trinh et al in their ab initio molecular dynamics simulations on the condensation of PAs in the existence of organic amines. These, consistent with early investigations on oligomerization of PAs, , evidenced dependence of the reaction thermodynamics and product selectivity of condensation on thermostability of PAs.…”
Section: Introductionsupporting
confidence: 81%
“…It is well-established in the literature ,, that the presence of ions can significantly influence the reaction kinetics and energetics. In this study, the obtained results indicate that the presence of Cl – has a noticeable effect on the overall activation barrier of the dimerization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The impacts of the charged ion have an important role in the silicate condensation reaction. For example, the organic cations (such as tetramethylamine (TMA + ), tetraethylamine (TEA + ), tetrapropyl amine (TPA + )) were shown to have a decisive role in the formation of dominating silicate spices during the initial state of zeolite formation. , A detailed picture of the interaction of inorganic cations (such as Li + , Na + , normalN normalH 4 + ) was also reported to have great impacts on the activation barrier of the condensation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, organic cations (such as tetramethylamine (TMA + ), tetraethylamine (TEA + ) and tetrapropylamine (TPA + )) were shown to have a decisive role in the formation of dominating silicate species during the initial stage of zeolite formation. 33,34 Computational studies indicated that inorganic cations (such as Li + , Na + and NH 4 + ) also have a substantial impact on the activation barrier of the condensation reaction. 25,28 Furthermore, pH is recognized as one of the most important parameters for controlling the kinetic and structural aspects of silicate oligomerization.…”
Section: Introductionmentioning
confidence: 99%